Cesarean Scar Pregnancy Presenting with Persistent Bleeding After Curettage: A Case Report of Uterine Resection and Reconstruction - Arfita, Ika; Septivera, Yusra (Syntax Literate, 2025)
Background: Cesarean scar pregnancy (CSP) is a rare and potentially life-threatening form of ectopic pregnancy in which the gestational sac implants within the myometrial scar from a previous cesarean section. It is associated with significant risks, including uterine rupture and severe hemorrhage. Case Presentation: We report the case of a 35-year-old multiparous woman (G5P4A1) with two prior cesarean deliveries who presented with persistent vaginal spotting for three weeks, worsening over the last three days. She had undergone uterine curettage for incomplete abortion three weeks prior. A transvaginal ultrasound revealed a hypoechoic mass in the cesarean scar niche, with positive vascularization, consistent with a diagnosis of CSP. Surgical intervention via laparotomy was performed, including evacuation of retained products of conception, uterine resection and reconstruction, bilateral tubectomy, and adhesiolysis. The patient recovered well and was discharged after three days of postoperative care. Conclusion: Early diagnosis and prompt surgical management of cesarean scar pregnancy are essential to prevent severe complications. This case emphasizes the importance of considering CSP in patients with prior cesarean sections presenting with abnormal uterine bleeding after early pregnancy loss.